Getting it right, a guide to improve inclusion in multistakeholder forums - Evans, K.; Monterroso, I.; Ombogoh, D.B.; Liswanti, N.; Tamara, A.; Mariño, H.; Sarmiento Barletti, J.P.; Larson, A.M. (Center for International Forestry Research, 2021)
This guide explains how to operationalize inclusion of women, Indigenous Peoples and other under-represented groups in multi-stakeholder forums (MSFs). Around the world, MSFs have been promoted and adopted as decision making, consultation and dialogue platforms to bring together diverse constituencies to share ideas and formulate decisions in a more open and equitable. Research finds that MSFs organizers believed that their forums foster equity simply by inviting more under-represented actors to the table; however, they spend less effort in addressing the power inequalities among participants and the quality of the participation and representation of historically under-represented groups. Getting it right focuses on the inclusion of women and Indigenous Peoples in natural resource management and governance contexts. In particular, we analyzed how these actors participate and/or are represented in spaces such as forest user group committees, co-management groups or forest commodity roundtable meetings. Our hope is that presenting cases of women and Indigenous Peoples provides insights into how different dimensions of social differentiation intersect in practice, pushing us to look at these different scales and inform us about other under-represented groups. Getting it right provides several tools that are designed to operationalize inclusion at specific trigger points where we believe action is most effective. Our goal with this guide is to present ideas, not solutions; the challenges to inclusion are complex, and unique to every MSF.